Clinical Relevance of HER-2/neu Overexpression in Patients With Testicular Nonseminomatous Germ Cell Tumor - Ghavamnasiri, Mohammad Reza; Saeedi Saedi, Hamid; Shahid Sales, Soodabeh; Ghafarzadegan, Kamran (Urology Journal, 2010)
Introduction: Recent scientific attention has focused on the role of growth factors in the progression of cancer. HER-2/neu is an epidermal growth factor receptor that is demonstrated to have correlation with poor prognosis of many cancers. This study evaluated the overexpression of HER-2/neu protein and its clinical importance in nonseminomatous germ cell tumors of the testis.Materials and Methods: Testis specimens of 54 patients with testicular nonseminomatous germ cell tumors, referred to Omid Hospital from 2001 to 2007, were re-evaluated and the patients’ records were reviewed. Patients’ age, tumor subtype, tumor stage, tumor markers, therapeutic response, and disease-free survival were assessed and the specimens were evaluated for the degree of HER-2/neu expression using an immunohistochemistry method.Results: Immunohistochemical staining was performed for 54 specimens. Overexpression of HER-2/neu was seen in 33.3% of the patients with nonseminomatous germ cell tumors, especially in those with teratocarcinoma subtype compared to those with mixed germ cell tumors or embryonal cell carcinoma. However, HER-2/neu overexpression did not show any correlation with tumor stage, therapeutic response, disease-free survival, age, beta-human chorionic gonadotropin, or ?-fetoprotein.Conclusion: We observed overexpression of HER-2/neu receptor in teratocarcinoma subtype of germ cell tumor. We suggest further studies to evaluate the clinical importance of this finding.